2017
DOI: 10.3390/polym9120638
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Human-Like Collagen Hydrogel Scaffold with Porous Structure and Sponge-Like Properties

Abstract: Abstract:The aim of this research was to prepare a novel sponge-like porous hydrogel scaffold based on human-like collagen (HLC) that could be applied in cartilage tissue regeneration. In this study, bovine serum albumin (BSA) was used as a porogen to prepare the porous hydrogel, which had not been previously reported. Glutamine transaminase (TGase) was used as the cross-linker of the hydrogel, because it could catalyze the cross-linking of BSA. During the crosslinking process, BSA and HLC were mixed together,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 43 publications
7
67
0
Order By: Relevance
“…In fact, the results obtained by swelling tests pointed out that, when immersed in PBS, the membranes rapidly swell and adsorb considerable liquid amounts immediately after soaking (Figure a). These results are in line with recent research studies stressing the importance of the porosity of polymeric scaffolding materials for cartilage repair applications and pointing out the importance of porous materials to guide the regeneration of a functional tissue (Browe et al, ; Nava, Draghi, Giordano, & Pietrabissa, ; Song et al, ). One of the advantages of the proposed system is that membranes formulation can be tailored to deliver variable amounts of the bioactive polysaccharide CTL at the lesioned site.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, the results obtained by swelling tests pointed out that, when immersed in PBS, the membranes rapidly swell and adsorb considerable liquid amounts immediately after soaking (Figure a). These results are in line with recent research studies stressing the importance of the porosity of polymeric scaffolding materials for cartilage repair applications and pointing out the importance of porous materials to guide the regeneration of a functional tissue (Browe et al, ; Nava, Draghi, Giordano, & Pietrabissa, ; Song et al, ). One of the advantages of the proposed system is that membranes formulation can be tailored to deliver variable amounts of the bioactive polysaccharide CTL at the lesioned site.…”
Section: Resultssupporting
confidence: 90%
“…This is also evident from the higher G′ values obtained for the stress‐sweep measurements in the case of C3M and corresponding hydrogels with respect to CTL 2% formulation. In line with these results, it has been recently reported that the swelling behavior of scaffolding materials for cartilage applications is influenced by the cross‐linking degree of polymer‐composing scaffolds (Song et al, ) and by material composition (Liao, Qu, Chu, Zhang, & Qian, ). During the swelling of the CTL‐based membranes, a dimensional increase can be observed from the first minutes (Figure b); the evaluation of the expansion upon hydration pointed out that, already during the first 20 min, an increase of membranes size in the range of 19–34% occurred (Figure b).…”
Section: Resultssupporting
confidence: 65%
“…On the contrary, if the pore size is too large, this may affect the mechanical property of scaffolds and the production of extracellular matrix on scaffolds [35,36]. Hence, the pore sizes of the nHD scaffolds were suitable for bone tissue engineering application, which were in accordance with previous studies about bone regeneration scaffolds [34,37]. Furthermore, the porosities of the composite scaffolds are also crucial elements for fabricating suitable scaffolds for bone tissue regeneration [34].…”
Section: Structure Of the Scaffolds Before And After Enzymatic Degradsupporting
confidence: 81%
“…13,14 Whereas hydrogel designs largely depend on the location of implantation (e.g., tissue type to be repaired or type of stem cell to be delivered), several design parameters can be manipulated to mimic the native ECM and consequently function to promote new tissue formation and stem cell engraftment (Figure 1). 15,16 On the most fundamental level, hydrogels should define a 3D space for tissue formation, as the 3D architecture can support the infiltration and assembly of host cells into structures and induce gene expression programs associated with normal growth or development. Cell seeding and infiltration of the hydrogel scaffold can be facilitated by micron-scale porosity and/or cell-mediated degradation cues introduced into the hydrogel design.…”
mentioning
confidence: 99%